The Role of Village Culture and Social Environment on the Behaviour of the Young Generation - Gultom, Gomgom Romauli; M Chaerul Rizky; Gerhard Grandnaldy Manurung; Khalisa Umaira Ismail; Dini Andriani Lubis; Puspita Wulandari (Al-Qalam Institue, 2025)
This study investigates the role of village culture and the social environment in shaping the behavior of the younger generation in Belawan Bahagia Village. Amid the challenges of modern social change, preserving local values and fostering a healthy social environment are considered essential. A quantitative approach with multiple linear regression was employed, using data from 66 young respondents selected through purposive sampling. Classical assumption tests—normality, multicollinearity, and heteroscedasticity—confirmed the feasibility of the regression model. The F-test results (Sig. = 0.000) indicate that both independent variables significantly influence youth behavior. Partial T-tests show that village culture (β = 0.494; Sig. = 0.000) has a more dominant effect than the social environment (β = 0.353; Sig. = 0.002). The findings underscore the importance of strengthening local cultural values and social cohesion as strategic efforts to foster responsible and constructive youth behavior. The study highlights the critical role of educational management in shaping youth behavior by integrating local cultural values and social norms into the curriculum and extracurricular activities. Therefore, educational policies and practices should prioritize academic achievement and the cultivation of ethical values and social cohesion among the younger generation. However, the study is limited to internal community factors and excludes broader external influences.